2014
DOI: 10.1093/omcr/omu004
|View full text |Cite
|
Sign up to set email alerts
|

Acute interstitial lung disease in a patient with anaplastic lymphoma kinase-positive non-small-cell lung cancer after crizotinib therapy

Abstract: Crizotinib, an orally active multi-targeted small-molecule anaplastic lymphoma kinase (ALK) inhibitor, is an effective treatment modality for advanced ALK-positive non-small-cell lung cancer (NSCLC). Most drug-related adverse events are mild to moderate; however, some patients may develop acute interstitial lung disease (ILD) which is sometimes fatal. We present a case of crizotinib-associated ILD in a 47-year-old woman treated with crizotinib for metastatic adenocarcinoma of the lung. The patient presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
(7 reference statements)
1
11
0
Order By: Relevance
“…After a systematic review of the literature, we identified 43 other cases of crizotinib-associated ILD, among which 34 were notified in the PROFILE studies and nine case reports described in more detail [10][11][12][13][14][15][16][17][18] (Table 3).…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After a systematic review of the literature, we identified 43 other cases of crizotinib-associated ILD, among which 34 were notified in the PROFILE studies and nine case reports described in more detail [10][11][12][13][14][15][16][17][18] (Table 3).…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
“…Other reported cases had few symptoms like ours (Table 3). 14,16,17 Crizotinib was restarted with corticosteroids, 12,16,17 except in one case. 14 This latter being the only which presented a relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinibinduced ILD is considered a rare event, 6 however, nowadays, there are more cases of Crizotinib-induced ILD reported, most of them in Asian patients with no related smoking exposure. 1,[7][8][9][10][11][12] Cough, fever and dyspnea may be present in patients with advanced NSCLC treated with TKIs, like in our case, but are usually non-specific. 3 In addition, the onset of pulmonary complications is unpredictable and there have been some life-threatening cases.…”
Section: Discussionmentioning
confidence: 49%
“…There was one grade 5 adverse event in the PROFILE 1014 trial, which was attributed to crizotinib-associated pneumonitis. Pneumonitis/interstitial lung disease of any grade is seen in approximately 2.5% of patients treated with crizotinib [19]. …”
Section: Therapeutic Optionsmentioning
confidence: 99%